Financial Reporting Quality and Accrual Accounting Disclosures: An Empirical Study on Regional Governments in Indonesia - Asrofa, Sadifa; Darwanis, Darwanis; Nuraini A, Nuraini A (Universitas Syiah Kuala, 2024)
Objective This research aims to investigate the quality of financial reporting and the extent of accrual accounting disclosure in Indonesia. Additionally, it examines the influence of capital expenditure budget, size, and age on the quality of financial reporting, with accrual accounting disclosure acting as a mediator.Design/Methodology The study was conducted by performing a textual analysis of 380 regional government financial reports in Indonesia. Data analysis was executed using the SEM-PLS method, facilitated by SmartPLS version 3.Results Although no LGFS achieved a perfect score for reporting quality, there was a notable improvement in the quality of financial reporting and accrual-based accounting disclosures in the LGFS from 2017 to 2021. The capital expenditure budget, the age of the local government and accrual accounting disclosures significantly affect the quality of financial reporting. Furthermore, accrual accounting disclosures mediate the effect of local government size on the quality of financial reporting.Research limitations/implications This research does not yet fully capture the quality of financial reporting and accrual accounting disclosures in Indonesia, as the study is limited to regional governments established in 2007. However, these findings can serve as a reference for local administrations striving to enhance the quality of their financial reporting and accrual accounting practices.Novelty/Originality This study complements existing research on the progression of accrual accounting in Indonesia through textual analysis and further examines how accrual accounting disclosures affect the quality of financial reporting, while mediating key factors within local Indonesian governments.